IDENTIFICATION OF RAPD AND ISSR MAKERS FOR RESISTANCE AGAINST MUNGBEAN YELLOW MOSAIC VIRUS IN MUNGBEAN (VIGNA RADIATA L.) UNDER SOUTH GUJARAT AGRO CLIMATIC CONDITION OF INDIA - R. K. KALARIA; DIGVIJAY CHAUHAN; MAHESH KUMAR MAHATMA; LALIT MAHATMA (The Bioscan, 2012)
The present study was undertaken to identify genetic variation and tightly linked marker associated with mungbean yellow mosaic virus (MYMV) resistance from different mungbean lines. Out of 200 RAPD markers, OPG-5, OPJ- 18 and OPM-20 were proved to be the best markers for the study of polymorphism as it produced 28, 35, 28 amplicons respectively with overall polymorphism was found to be 70.17 %. Out of 17 ISSR markers used, DE- 16 proved to be the best marker as it produced 61 amplicons and 15 scorable bands and showed highest polymorphism among all. The combined dendrogram obtained from these RAPD and ISSR indicated two clearly visible clusters where all resistant lines viz., NAUMR1, NAUMR2, NAUMR3 and MEHA clearly separated from susceptible GM4. Here validation of these data could be compare with phenotypic character in the field. Once these markers are identified, they can be used to detect the QTLs linked to MYMV resistance in mungbean breeding programs, as a selection tool in early generations and further use in developing segregating material.